Model of Sustainable Private Forest Management in Yogyakarta Special Regency, Indonesia - budi widayanto; Ravik Karsidi; Kusnandar Kusnandar; Joko Sutrisno (Journal of Agricultural Extension, 2019)
The study analysed the relationships between variables i.e. community empowerment, community institutions, stakeholder support, farmer participation in the management of private forests, and generate a sustainable private forest management model. The research method was the survey method with the area sample taken with purposive sampling and farmer samples taken with multistage random sampling resulting in 270 samples. Data collected were analysed using descriptive statistics and structural equation model. The results of the study show that sustainable private forest management is directly influenced by farmer participation (0.65), community institutions (0.20), and stakeholder support has no direct influence (0.07). Stakeholder support indirectly influence sustainable private forest management through mediation variable (0.39). This study found that community compliance with the value of local institution, where private forests are the ancestral heritage that must be preserved can change the harvest system that considers sustainability aspects.